Pengaruh Motivasi Dan Kepuasan Kerja Terhadap Disiplin Kerja Pegawai Administrasi Di Rsud Ulin Banjarmasin - R Rohana; Misransyah Akos (STIA Bina Banua Banjarmasin, 2019)
This study aims: 1) to analyze regression of motivation on the discipline of Administrative Staff work at Ulin Banjarmasin Hospital; 2) to analyze regression of job satisfaction on the discipline of Administrative Staff work at Ulin Banjarmasin Hospital. The study uses descriptive quantitative methods. The research population is Administrative Staff who work in Ulin Banjarmasin Hospital, both Civil Servants (PNS) and Non Civil Servants (Non PNS), all of which are 105 (one hundred and five) people. Samples totaling 82 people. The independent variable is motivation and job satisfaction while the dependent variable is work discipline. Data collected using questionnaires. Data analysis using multiple linear regression statistical tests with a significant level of 0.05. The results of this study indicate 1) there is regression between motivation towards work discipline of 0,000. 2) there is regression between job satisfaction and work discipline of 0.007. Conclusion: motivation has a significant regression on the work discipline of administrative employees in the Banjarmasin Ulin Regional General Hospital. While the motivation variable regression coefficient is positive; Job satisfaction significantly regression the work discipline of administrative employees in the Banjarmasin Ulin Regional General Hospital. While the regression coefficient of job satisfaction variable is positive. Suggestion: that is the placement of staff according to their expertise, training and seminars on a regular basis, management makes work discipline policies so that the goal of Ulin Banjrmasin Hospital is reached. Penelitian ini bertujuan : 1) untuk menganalisis pengaruh motivasi terhadap disiplin kerja Pegawai Administrasi di RSUD Ulin Banjarmasin; 2) untuk menganalisis pengaruh kepuasan kerja terhadap disiplin kerja Pegawai Administrasi di RSUD Ulin Banjarmasin. Penelitian menggunakan metode deskriptif kuantitatif. Populasi penelitian adalah Pegawai Administrasi yang bekerja di RSUD Ulin Banjarmasin, baik Pegawai Negeri Sipil (PNS) mupun Non Pegawai Negeri Sipil (Non PNS) , yang semuanya berjumlah 105 (seratus lima) orang.Sampel berjumlah 82 orang. Variabel bebas adalah motivasi dan kepuasan kerja sedangkan variabel terikat adalah disiplin kerja. Data yang dikumpulkan dengan menggunakan angket. Analisa data menggunakan uji statistik regresi linier berganda dengan taraf signifikan 0,05. Hasil Penelitian ini menunjukkan 1) ada pengaruh antara motivasi terhadap disiplin kerja sebesar 0,000. 2)ada pengaruh antara kepuasan kerja terhadap disiplin kerja sebesar 0,007. Motivasi berpengaruh secara signifikan terhadap disiplin kerja pegawai administrasi di lingkungan Rumah Sakit Umum Daerah Ulin Banjarmasin. Sedangkan koefisien regresi variabel motivasi bernilai positif; kepuasan kerja berpengaruh secara signifikan terhadap disiplin kerja pegawai administrasi di lingkungan Rumah Sakit Umum Daerah Ulin Banjarmasin. Sedangkan koefisien regresi variabel kepuasan kerja bernilai positif.